Yield and Nutritive Value of Palmyrah (Borassus flabellifer) Leaves at Different Stages of Maturity - Sarmini, M.; Premaratne, S. (University of Jaffna, 2018)
Present study was conducted to evaluate the yield and nutritive value of palmyrah (Borassus flabellifer) leaves at different growth stages to find out its forage nutritive value. Palmyrah leaf samples were collected from three male and female palms at seven growth stages (5, 10, 15, 20, 25, 30 and 35 months). Fresh and dry matter weights of the leaves were measured. Dried leaves were ground into 1 mm particles and analyzed for their nutrient composition using standard procedures. There was no significant difference (p>0.05) between male and female palms for most of the parameters studied (dry matter (DM), crude protein (CP), crude fiber (CF), ash and gross energy (GE). Leaf weight varied from 0.91 to 1.22 kg/leaf and 0.91 to 1.30 kg/leaf (DM basis) in male and female palms, respectively. The range of values of nutrient composition of leaves from male and female palms were: CP 10.1-14.4% and 10.1-14.4%; CF 35.5 – 48.1% and 35.7 – 49.3%; calcium (Ca) 1.34 – 4.30% and 1.52 – 4.53% and phosphorous (P) 0.24 – 0.44% and 0.20 – 0.4 0%, respectively. In vitro dry matter digestibility (IVDMD) and GE were ranged between 39.72 – 53.99% and 38.06 – 51.28% and 4.35 – 4.55 Mcal/kg and 4.37 – 4.61 Mcal/kg for leaves of male and female palms, respectively. The CP, IVDMD, GE and phosphorus contents were decreased with advancing maturity, whereas, CF and Ca were increased. Accordingly, leaves harvested from both male and female palms at 10 to 30 months of age have a good forage value in terms of CP, IVDMD and fodder yield to be used as ruminant feed
Keywords: forage-value; growth-stages; leaf weight; nutrient composition